A sexualidade, a literatura para jovens e a obra Quinze dias : a literatura é toda nossa - Potrick, Anderson (2025)
The theme of this dissertation is the presence of homosexuality in contemporary young adult literature. With this in mind, we set ourselves the objective of investigating the narrative construction of the novel Quinze Dias, by Vitor Martins (2022), with homosexual themes from the LGBT+ community aimed at a young audience. We considered looking at the work beyond issues of narrative construction, but also at the social character that a work that presents a story of diversity presents as a way of welcoming a minority community. We built the research on theories by Lucia Facco (2009) when we understood youth literature with a homosexual theme, Michael Foucault (1983) when we studied issues related to sexuality, Jack Halberstam (2020) to reflect on Queer experiences, Judith Butler (2018) to talk about gender and sexuality and their social performances, as well as various authors to support issues related to literature. We seek to analyse Quinze Dias to understand how the narrative is constructed, by mobilizing bibliographic theoretical concepts, developing an explanatory production that links the theoretical concepts with the contemporary work in a qualitative way, with an important literary analysis considering the theme and the historical moment in which we are inserted. We conclude that the work reinforces a narrative model of homosexual works that usually provides a welcoming space for stigmatized readers.